Modified total indoor composting techniques using thermophilic fungi - Pathak, A; Vijay, B; Singh, S (Mushroom Research, 2013)
Laws governing pollution are become stringent day by day in the country and many a units even producing compost either by long, short and indoor methods (bunker technology) are facing environmental issues as long or short period of phase-I in windrow or bunker pollutes the atmosphere and create nuisance for nearby residents. To overcome these issues a new method of composting called modified indoor composting technique was adopted in which phase-I of composting was altogether escaped. In this technique whole compounding mixture was initially sterilized in the phase-II tunnel and then was inoculated with potent strains of Scytalidium thermophilum (S-7) and Humicola insolens (I-1) and their consortium. Good quality compost was produced by this technique in eight days time only, giving a conversion ratio in the range of 2.87 to 3.36 in different treatments. Highest fruit body yield in the experiment was recorded in consortium treatments (19.06 kg / 100kg compost), followed by isolate I-1 treatment (18.94 kg) compared to control which yielded 16.13 kg of mushrooms. Comparative results were also analyzed for each treatment in terms of population dynamics of thermophilic fungi and various physico-chemical properties at different stage of compost preparation. Data obtained indicated that highest reduction in C/N ratio, hemicellulose and cellulose was observed in inoculated treatments as compared to control treatment. New technique improved the consistency of compost quality, gave more compost per unit wt. of ingredients taken and higher fruit body yields with no or minimum environment pollution. Such technique will be a boon for those who are facing environment related issues and they will be able to produce productive compost in as less in eight days time.